Correlation of Some Dielectric Properties with Processing and Microstructure in Mg-Sn-O System - Ahmad Taha, Iftetan; Hashim, Mansor (1999)
The alkaline-earth stannates having the general chemical formula MSn03 (M = Ca, Sr and Ba), have been projected as potential electronic ceramics (thermally stable capacitors, humidity sensor, carbon dioxide sensor, etc.). Even though magnesium is a member of the metal group to which Ca, Sr and Ba belong, no reliable technical information on the compounds in the pseudo-binary MgO-SnO₂ system appears to exist in the published literature. In view of the information gaps in the reported research, vigorous and systematic investigation has been carried out on the MgO-SnO₂ system. The MgO-SnO₂ system has been thoroughly studied with respect to synthesis, processing and characterisation - physical, microstructural and electrical. Two different synthesis routes have been adopted. These routes are solid-state and self-he atsustained. For each route two mixtures of different molar ratio viz., 2:1 and 1:1 have been used. In 2:1 molar ratio mixtures MgzSnO₄ has been formed as a single phase upon calcination of starting materials at 1200°C/24 h in both solid-state and self-heatsustained techniques with one or two impurity peaks at 1200°C/ 24 h. In 1:1 molar ratio, the reaction product consisted of a two-phase mixture of Mg₂SnO₄ and SnO₂. Evaluation of microstructure that is intimately related to the envisaged properties in the ceramics has been closely and systematically followed as a function of sintering at different temperatures of (1200- 16000°C) and soak - time (2-48 h). A thorough analysis of the as measured electrical data showed that the material possessed a very weak temperature dependence of capacitance (TCC) and dielectric constant (TCK) in the range 27-300°c over several decades of frequency domain. It was found that TCC value varied between (-200 to +195) ppm IK thus holding the promise to its usage as a thermally stable capacitor component in high-speed electronic devices. The average dielectric constant was found to be in the range 10-18, thus identifying this material as a low dielectric constant system as well.